Chronic myeloid leukemia as a stem cell-derived malignancy - Babashah, Sadegh; Rezaei-Tavirani, Mostafa; Zamanian-Azodi, Mona; Saki, Najmaldin (Archives of Advances in Biosciences, 2012)
Chronic myeloid leukemia (CML) is a myeloproliferative disease of the hematopoietic stem cells, characterized by the presence of the Philadelphia (Ph) chromosome. Although imatinib inhibits the BCR-ABL kinase activity, clinical experiences confirm that imatinib may not target CML stem cells in vivo. The identification of signaling pathways responsible for the self-renewal properties of leukemic stem cells in CML will help in the discovery of novel therapeutic targets. Here we review signaling pathways including Wnt/β-catenin, Hedgehog, Alox5, and Foxo which play crucial roles in the maintenance of stem cell functions in CML. It is thought that inhibition of key genes that are part of self-renewal associated signaling pathways may provide an effective way to reduce aberrant stem cell renewal in CML.